2D Functionalized Germananes: Synthesis and Applications. Issue 7 (28th December 2022) - Ng, Siowwoon; Pumera, Martin
Abstract: In the realm of 2D layered materials, the monoelemental group 14 Xene, germanene, as the germanium analog of graphene, has emerged as the next prospective candidate. Preceded by silicon, germanium is widely used in the semiconductor industry; thus, germanene is deemed compatible with existing semiconductor technologies. Germanene consists of mixed sp 2 –sp 3 ‐hybridized networks in a buckled hexagonal honeycomb structure. Chemical exfoliation of Zintl phases, such as CaGe2, specifically the topotactical deintercalation in acidic media, removes the alkaline earth metal ions Ca 2+, giving rise to layered germanane (germanene with the Ge centers covalently saturated with terminal hydrogen atoms). Diverse variants of functionalized germananes (with covalent group(s) termination) can be obtained by varying the topotactical deintercalation precursors, elevating the game with limitless functionalization possibilities for customizable properties or new functionalities. The preparation of Zintl phases to the details of functionalized and modified germananes and their properties, and the additional exfoliation step to achieve mono‐ or few‐layer germananes, are comprehensively covered. The progress and challenges of 2D functionalized germananes in optoelectronics, catalysis, energy conversion and storage, sensors, and biomedical areas are reviewed. This review provides insight into designing and exploring this class of atomically thin semiconductors in realizing future nanoarchitectonics. Abstract : Chemical synthesis and functionalization of 2D germananes (hydrogen atom and covalent group(s) termination) via topotactical deintercalation offer customizable properties or new functionalities. The fundamentals from synthesis and exfoliation to properties; for optoelectronics, catalysis, energy conversion and storage, sensors, and biomedical applications are reviewed. The review presents the recent progress and challenges, and provides insight for future exploration of these materials.